Conducting EEG research in clinically anxious preschoolers: A pilot study and preliminary recommendations. Issue 7 (14th September 2021) - Horbatch, Faith; Hruschak, Jessica; Hall, Melissa; Mannella, Kristin A.; Synger, Ashley; Ip, Ka I.; Liu, Yanni; Sadlier, Raleigh; Gillett, Carrie B.; Moser, Jason S.; Muzik, Maria; Rosenblum, Katherine L.; et al.
Abstract: Electroencephalography (EEG) data collection can be challenging in preschoolers with anxiety who are often debilitated by fear of the unknown. Thus, we iteratively refined techniques for EEG collection in three cohorts of children with anxiety enrolled in our study of a novel intervention. Techniques involved directing child attention away from the EEG setup (Cohort 1, N = 18), open discussion of equipment and processes during setup (Cohort 2, N = 21), and a preparatory EEG‐exposure session prior to data collection (Cohort 3, N = 6). Children ( N = 45, 4–7 years) attempted a Time 1 EEG before intervention, and those who completed intervention ( N = 28) were invited to a Time 2 EEG. The percentages who provided analyzable EEGs were assessed by cohort. Cohort 3 provided more Time 1 EEGs (83.3%) than Cohorts 1 or 2 (66.7% each), suggesting that the preparatory session supported first‐time EEG collection. More children provided Time 2 EEG data across successive cohorts (Cohort 1: 66.7%, Cohort 2: 82%, Cohort 3: 100%), suggesting that more open communication facilitated repeat EEG collection. Ultimately, increased EEG exposure and child‐friendly communication about procedures improved data acquisition in this sample of clinically anxious preschoolers. Detailed study procedures are shared to support future EEG research in young children with anxiety.